A Cytidine Phosphoramidite with Protected Nitroxide Spin Label: Synthesis of a Full‐Length TAR RNA and Investigation by In‐Line Probing and EPR Spectroscopy. Issue 23 (6th April 2018) - Weinrich, Timo; Jaumann, Eva A.; Scheffer, Ute; Prisner, Thomas F.; Göbel, Michael W.
Abstract: EPR studies on RNA are complicated by three major obstacles related to the chemical nature of nitroxide spin labels: Decomposition while oligonucleotides are chemically synthesized, further decay during enzymatic strand ligation, and undetected changes in conformational equilibria due to the steric demand of the label. Herein possible solutions for all three problems are presented: A 2‐nitrobenzyloxymethyl protective group for nitroxides that is stable under all conditions of chemical RNA synthesis and can be removed photochemically. By careful selection of ligation sites and splint oligonucleotides, high yields were achieved in the assembly of a full‐length HIV‐1 TAR RNA labeled with two protected nitroxide groups. PELDOR measurements on spin‐labeled TAR in the absence and presence of arginine amide indicated arrest of interhelical motions on ligand binding. Finally, even minor changes in conformation due to the presence of spin labels are detected with high sensitivity by in‐line probing. Abstract : Spin labels stabilized : Nitroxides are important spin labels for EPR studies on biopolymers, but sample preparation can be severely restricted by their limited chemical stability. The 2‐nitrobenzyloxymethyl group protects the TEMPO spin label against all critical conditions of chemical RNA synthesis and enzymatic ligation (see figure). After photochemical deprotection, the nitroxide radical is recovered by spontaneous air oxidation. Assembly of a spin‐labeled 59mer RNA is shown as an example.